Benign external hydrocephalus and its relation to familial megalencephaly: An analysis of 20 cases - Karimzadeh, Parvaneh; Tonekaboni, Seyed H.; Shariatmadari, Fakhreddin (Journal of Pediatric Neurology, 2009)
Benign idiopathic external hydrocephalus (BIEH) is an age dependent, self-limited disorder with uncertain etiology. In this study, we aimed at confirming the benign nature of this disease, focusing on avoidance of unnecessary surgical intervention, relation to benign familial macrocephaly and prevention of head trauma. In Mofid children's hospital, between September 2005 and September 2007, 20 infants, aged less than 1 year of age, were diagnosed with BIEH, on the basis of macrocephaly and brain computerized tomography (CT) scan findings, which all infants underwent at the beginning of the study; the results revealed a large subarachnoid space. These infants were studied, keeping in mind familial megalencephaly, birth history, head growth, developmental prognosis and development of subdural hematoma. All children were followed prospectively for 12 months. For all infants, CT scans were repeated after 6 and 12 months. There were 14 (70%) boys and six (30%) girls; of these 20 infants, 18 (90%) infants showed variable degrees of mild gross motor developmental delay, while two (10%) had normal development. In all infants, the head circumference was greater than the 90th percentile; 17 of the fathers also had macrocephaly. After 12 months of follow up, all the infants were observed to be developing normally. One infant was found to have frontal subdural hematoma in association with prominent extracerebral cerebrospinal fluid spaces with no history of major trauma or risk factors for child abuse. CT scans, repeated after 12 months, showed resolution of the process in 14 (70%) cases, improvement in five (25%) and no change in one (5%). Considering that at the initiation of our study, 90% of infants had variable degrees of mild gross motor developmental delay, and in follow up, all the infants were developing normally, it can be concluded that BIEH is a benign, self-limited condition that resolves without treatment and is closely related to benign familial macrocephaly. Finally suggest idiopathic external hydrocephalus could rarely predispose to the development of subdural hematoma with minimal or no trauma.
Keywords: External hydrocephalus; developmental prognosis; familial macrocephaly